Análise quantitativa da implantação de programa de garantia da qualidade em equipamentos de raios-X instalados na região de Araçatuba-SP - Fernandes, Marco Antonio Rodrigues [UNESP]; Nagamatsu, Rafael Yukio; Castelli, Natália Cristina; Nascimento, Marcos Vinicius (My University, 2011)
This work illustrates the importance of accomplishing Quality Assurance Program equipments issuing of ionization radiation, used in radiological exams. The results of alalysis of 4.273 technical reports emitted among the years from 1996 to 2010 are presented. The radiometric parameters demanded by the effective legislation on radiological protection, were quantified fo the radiation beams studied. The results show that the apparels that presented some disconformities went being appropriate or substituted, reinforcing the need of the continous orientation of the professionals that use these equipments, as the precepts of radiological protection.

Este trabalho ilustra a importância de se realizar Programas de Garantia da Qualidade em equipamentos emissores de radiação ionizante, utilizados em exames de radiodiagnósticos. São aprsentados os resultados de análise de 4.273 relatórios técnicos emitidos entre os anos de 1996 a 2010. Os parâmetros radiométricos exigidos pela legislação vigente sobre proteção radiológica foram quantificados para os feixes de radiação estudados. Os resultados mostram que os equipamentos que apresentaram alguma desconformidade foram sendo adequados ou substituídos, reforçando a necessidade de orientação contínua dos profissionais que utilizam estes equipamentos e os preceitos de proteção radiológica.
Quantitative analysis of the implantation of quality assurance program in equipments of medical and dental X-ray installed in the region of Araçatuba-SP
Keywords: Quality control; Radiometry; X-ray; Sanitary surveillance; Controle de qualidade; Radiometria; Raios-X; Vigilância sanitária